Effectiveness of Homeopathic Individualized Treatment in Pemphigus Vulgaris - A Case Report (Advancements in Homeopathic Research, 2022)
Background Pemphigus Vulgaris is an autoimmune disease of your skin and mucous membranes. Pemphigus Vulgaris lesions begins with blisters in your mouth and then on your skin or genital mucous membranes. It tends to be a long-lasting (chronic) condition, and some types can be life-threatening without treatment. A 56 yrs old male patient was diagnosed with Pemphigus Vulgaris. He had skin eruptions which were painful and oozing honey like discharges. It begun with painful oral blisters, followed by skin lesions. He had taken allopathic treatment with no relief. After prescribing homeopathic remedy on basis on similimum with classical approach, the patient showed remarkable improvement. Method-A single chronic clinical case of Pemphigus Vulgaris was treated with an individualised homeopathic treatment, without aid of conservative treatment. Result- The patient recovered remarkably with Homeopathic therapy. Interpretation-Homeopathy has and hope in treating Pemphigus Vulgaris where conservative treatment failed to give positive results. Conclusion-Homeopathic therapy was observed to treat Pemphigus Vulgaris with a gentle approach in a patient, which is routinely treated with corticosteroids.
Keywords: Pemphigus Vulgaris; autoimmune disease; homeopathic treatment